The Ascetic Aesthete: How Ascetism is the Right Relationship to Beauty, Real Care for the Self, and Love for the World - Hayes, Alexandra (The Nordic Journal of Aesthetics, 2025)
What is the role of beauty for the individual navigating the modern world? What does it say about the moral status of people, the value of matter, and the relationship between the two? I will argue that the right relationship to beauty is an ascetic one, a practice of saying no to the self, in order to truly care for the self and love the world. This is a matter of constant training, re-evaluating, and witnessing ourselves and the world